2024
DOI: 10.1021/acs.jpcc.3c07943
|View full text |Cite
|
Sign up to set email alerts
|

Novel Deuterated Benzothiadiazole Derivatives with Enhancing High-Lying Reverse Intersystem Crossing for High-Efficiency Organic Light-Emitting Diodes

Xiangyu Dong,
Shaogang Shen,
Yuanyuan Qin
et al.

Abstract: Developing efficient "hot exciton" thermally activated delayed fluorescence (TADF) materials in electroluminescence has always been a significant and challenging issue. Herein, we have designed and synthesized two deuterated yellow emitters BT-2PhCz-d 10 and BT-2PhCz-d 24 based on the commonly designed hot exciton emitter BT-2PhCz to improve the exciton utilization efficiency. Transient absorption (TA) kinetic analysis showed that deuterated BT-2PhCz-d 10 and BT-2PhCz-d 24 possessed shorter delayed lifetimes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…BTD derivatives also display slow photodynamics due to the existence of accessible triplet states. 62,66,67,74 Our results from the theoretical calculations on BTIA-ester in DMF (Section 3.1) show the possibility of an ISC process between the S 1 and T 2 states (Δ E S 1 / T 2 = 0.326 eV), leading to species which may populate the T 2 state. To explore the slow relaxation of BTIA-ester and BTIA-COOH in DMF solutions, we carried out ns–ms flash photolysis experiments upon excitation at 355 nm in presence and absence of molecular oxygen.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…BTD derivatives also display slow photodynamics due to the existence of accessible triplet states. 62,66,67,74 Our results from the theoretical calculations on BTIA-ester in DMF (Section 3.1) show the possibility of an ISC process between the S 1 and T 2 states (Δ E S 1 / T 2 = 0.326 eV), leading to species which may populate the T 2 state. To explore the slow relaxation of BTIA-ester and BTIA-COOH in DMF solutions, we carried out ns–ms flash photolysis experiments upon excitation at 355 nm in presence and absence of molecular oxygen.…”
Section: Resultsmentioning
confidence: 88%
“…61 Comparable energy gap values (Δ E S 1 / T 2 = 0.277 eV and Δ E T 1 / T 2 = 0.972 eV) have been observed in other BTD derivatives, which undergo a RISC process. 62 The HOMO−1 transition involved in the T 2 state exhibits significantly higher contributions from the BZ fragment and sulphur atom, with a lesser contribution from the MBZ moiety compared to the HOMO transition associated with the S 1 state. This results in considerable differences in the CT character of the S 1 and T 2 states.…”
Section: Resultsmentioning
confidence: 97%
“…The devices based on perdeuterated emitters exhibit a EQE max of 33.1% and a lifetime to reach 80% of the initial luminance of 1365 h with a CIE y coordinate of 0.20 at a luminance of 1000 cd m –2 , which outperforms blue PHOS OLEDs. Recently, we found that the introduction of deuterium atoms could become an efficient strategy for designing high-performance hot exciton emitters. Two deuterated emitters, BT-2PhCz-d10 and BT-2PhCz-d24 , based on the commonly designed hot exciton emitter BT-2PhCz were designed and synthesized.…”
Section: Limitations and Progressmentioning
confidence: 99%